A Medieval Boom in the North-west Sahara. (16th February 2022) - Fenwick, Corisande; Sterry, Martin; Mattingly, David J.; Rayne, Louise; Bokbot, Youssef
Abstract : Modern scholarship on the medieval Sahara has focused on a handful of famous entrepôt sites that have their origins in the 8th century or later, and as a result we still understand very poorly the nature and extent of Saharan oasis settlement and agriculture in the golden age of Saharan trade. This article presents the first securely dated chronology for oasis development in the north-west Sahara based on three seasons of archaeological survey and a comprehensive radiocarbon dating programme in the Wadi Draa, Morocco. The Draa Valley contains some of the largest, most populous and most productive oases in the Sahara, as well as serving as an important travel corridor for trading caravans coming from West Africa to access the Atlas passes and reach Marrakech. Focusing on evidence from a large zone of abandoned oases on the Kasr Bounou Plain, this article demonstrates that while oasis agriculture and settlement was taking place between the 4th–8th centuries—well before the Muslim conquest of Morocco—there was a significant increase in settlement and agricultural exploitation from the 9th century. This phenomenon is marked by the appearance of substantial mudbrick settlements, along with irrigation and field systems, and is coterminous with the development of the medieval trading entrepôt of Sijilmasa. A settlement boom and significant investment in irrigated oasis agriculture occurred between the 11th and 13th centuries, contemporary with Almoravid and Almohad rule of the Draa, followed by a retraction and abandonment of much of the oasis by the 16th century. The new evidence from the Draa challenges the long-held belief that sedentarization and irrigated oasis agriculture were unique to the medieval period in the north-west Sahara.   OPEN ACCESS CC BY-NC-ND